A feasibility study of a physical activity intervention for people with severe mental illness in medium secure psychiatric services in the United Kingdom - Roden-Lui, Gloria; Faulkner, Guy; Lucock, Mike; Gibbon, Simon; Hewitt, Catherine; Hughes, Elizabeth; Khan, Wajid; Lewis, Kiara; Singh, Bal; Walters, Phil; Watson, Judith; Walker, Tammi (Frontiers in Psychiatry, 2025)
BackgroundIn the UK, there are approximately 3500 individuals detained in medium secure service. Service users in such settings have complex and severe mental illness (SMI), often with co-morbid physical health problems, shorter life expectancy and low levels of physical activity (PA). However, there are few studies about PA interventions for medium secure service users in the United Kingdom. Therefore, the aim of the study was to co-produce, with medium secure service users and staff, the content and delivery of an intervention to increase PA.MethodsA feasibility and acceptability study were conducted to test the PA intervention using the Capability, Opportunity, Motivation Behaviour Change Model (COM-B model) as the underpinning theoretical model. Both female and male service users, with personality disorder and/or mental illness, were recruited from two medium secure services in the UK.Outcome measures were collected at baseline, after the intervention and at follow up (3-months after intervention), and included PA levels, mental well-being, data on recruitment and retention and causes of drop out.ResultsA total of 33 participants were recruited. Seven participants withdrew during the intervention period and 26 participants completed the PA intervention. During the follow up stage, three participants withdrew. Following the intervention participants increased PA and improved physical health and wellbeing. Overall, there was good retention for the PA interventionConclusionRetention rates and completeness of data at both study sites indicate that it is feasible and acceptable to co-produce, deliver and maintain commitment to a PA intervention in such settings for service users with SMI. A future pilot randomised controlled trial (RCT) will allow further understanding about the effectiveness of the PA intervention in medium secure psychiatric services.Clinical trial registrationhttps://doi.org/10.1186/ISRCTN15546527, ISRCTN Registry – ISRCTN15546527.